Analisis Campur Kode Dalam Film Preman Pensiun Serta Pemanfaatannya Sebagai Bahan Ajar Di Kelas XI SMA - Ricky Sukandar; Fitri Septiani R; Laksmita Nur Afiati (Journal on Education, 2024)
This reaserch is entitled "Analysis of Code Mixing in the Preman Pensiun movie and Its Use as Teaching Material in Class XI Senior High School". The aims of this study is to describe the analysis of code mixing in the Preman Pensiun movie as well as its interpretation as a teaching material in the Class XI of senior high school. This research uses a qualitative approach, with research methods of descriptive analysis. The data gathering techniques in this study covered free-to-speech swing techniques. As a result of the analysis of this study, there was a mixed-language variation of code in the Preman Pensiun movie and it was used in the form of e-module teaching materials through flip book media.